The Importance of Demographics in Explaining Attainment Patterns - Hauptman, Arthur M (International Higher Education, 2014)
This article examines the role that demographics and population trends play in determining attainment rates in countries around the world.  For the U.S., consistent increases over time in the numbers of degrees awarded have been offset by increases in birthrates among minority groups and immigration among poorly educated workers, both of which tend to depress the attainment rate.  By contrast, many of the countries that have overtaken the U.S. in their higher education attainment rates have declining numbers of young adults.  This means that they are educating a higher share of a declining base of workers which will have adverse effects on their ability to meet their labor force needs in the future.